Lymphovascular and perineural invasion as selection criteria for adjuvant therapy in intrahepatic cholangiocarcinoma: a multi-institution analysis - Fisher, Sarah B (Blackwell Science Inc, 2012)
OBJECTIVES: Criteria for the selection of patients for adjuvant chemotherapy in intrahepatic cholangiocarcinoma (IHCC) are lacking. Some authors advocate treating patients with lymph node (LN) involvement; however, nodal assessment is often inadequate or not performed. This study aimed to identify surrogate criteria based on characteristics of the primary tumour. METHODS: A total of 58 patients who underwent resection for IHCC between January 2000 and January 2010 at any of three institutions were identified. Primary outcome was overall survival (OS). RESULTS: Median OS was 23.0 months. Median tumour size was 6.5 cm and the median number of lesions was one. Overall, 16% of patients had positive margins, 38% had perineural invasion (PNI), 40% had lymphovascular invasion (LVI) and 22% had LN involvement. A median of two LNs were removed and a median of zero were positive. Lymph nodes were not sampled in 34% of patients. Lymphovascular and perineural invasion were associated with reduced OS [9.6 months vs. 32.7 months (P= 0.020) and 10.7 months vs. 32.7 months (P= 0.008), respectively]. Lymph node involvement indicated a trend towards reduced OS (10.7 months vs. 30.0 months; P= 0.063). The presence of either LVI or PNI in node-negative patients was associated with a reduction in OS similar to that in node-positive patients (12.1 months vs. 10.7 months; P= 0.541). After accounting for adverse tumour factors, only LVI and PNI remained associated with decreased OS on multivariate analysis (hazard ratio 4.07, 95% confidence interval 1.60–10.40; P= 0.003). CONCLUSIONS: Lymphovascular and perineural invasion are separately associated with a reduction in OS similar to that in patients with LN-positive disease. As nodal dissection is often not performed and the number of nodes retrieved is frequently inadequate, these tumour-specific factors should be considered as criteria for selection for adjuvant chemotherapy.